The making of minjung : democracy and the politics of representation in South Korea - Lee, Namhee (Cornell University Press, 2007)
"In this intellectual and cultural history of the minjung ("common people's") movement in South Korea, [author] shows how the movement arose in the 1970s and 1980s in response to the repressive authoritarian regime and grew out of a widespread sense that the nation's "failed history" left Korean identity profoundly incomplete. [book title] captures this movement in its many dimensions, presenting its intellectual trajectory as a discourse and its impact as a political movement, as well as raising questions about how intellectuals represented the mingjung."--Jacket